Combination of ultracentrifugation and solid-phase extraction with subsequent chromatographic analysis of α-tocopherol in erythrocyte membranes - Plíšek, Jiří; Pospíchalová, Naďa; Khalikova, Maria; Aufartová, Jana; Solichová, Dagmar; Krčmová, Lenka Kujovská; Solich, Petr (Journal of separation science, 2015)
A novel and rapid sample pretreatment technique based on a combination of ultracentrifugation and solid-phase extraction for the determination of α-tocopherol in human erythrocyte membranes by high-performance liquid chromatography with ultraviolet detection is presented in this work. Red blood cell samples were ultracentrifuged (288 000 × g, 3 min, 4°C) in the presence of d-mannitol, 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid and calcium chloride. The α-tocopherol was then extracted from the erythrocyte membranes by solid-phase extraction with n-hexane in the presence of ascorbic acid. Tocopherol acetate was used as the internal standard. The extract was dissolved in methanol and separated on the monolithic column Chromolith Performance RP-18e (100 × 4.6 mm) using 100% methanol as the mobile phase. The absorbance of α-tocopherol was measured at a wavelength of 295 nm. The method was validated and showed sufficient accuracy and precision, ranging from 96.4 to 100.8% and from 4.5 to 6.3%, respectively. Moreover, the developed method was applied to the determination of erythrocyte α-tocopherol in real samples from patients. The combined ultracentrifugation and solid-phase extraction technique substantially decreased the time for the sample pretreatment step compared to liquid-liquid extraction and could be applicable for the quantitation of other analytes in erythrocyte membranes.
Keywords: Solid-phase extraction; Ultracentrifugation; Erythrocyte membranes; Alpha-tocopherol; Red blood cells